An Empirical Study of the Social Economic Impact of Federal Polytechnic on its Host Community - Jenyo, G. K.; Adebayo, Ola (American Journal of Humanities and Social Sciences, 2013)
<!--[if gte mso 9]> <![endif]--> A polytechnic, sited in a metropolitan environment especially, is regarded among other things as a veritable citadel of learning and vehicle for social – economic emancipation of the people. Not only that the institution be a source of light into the darkness of ignorance, poverty and disease, but it will also provide gainful employment opportunities to its patrons, through its many linkages which will inevitably spring up overtime. Host communities to such institutions are usually seen as the primary beneficiaries, if the opportunities thus provided are effectively harnessed. The corollary also holds that if a gap exists by omission or commission, between the expected and actual outcomes regarding the project’s impact on the host community, the credibility gap also widens. The wisdom in releasing their land for such projects. This study was undertaken to examine to what extent the Offa community was justified in hosting federal Polytechnic, vis-a-viz the economic impact that the latter is making on its host community. A survey research design was used while stratified sampling techniques were employed in selecting the sample, realizing the heterogeneous nature of the parameters employed. 50 questionnaires were distributed but only 34 were completed and returned which represented 68% response rate. Data collected were summarized using frequency tables while Pearson correlation analyses was further done to test the hypothesis that the establishment of Federal Polytechnic at Offa has not made any significant impact on the socio-economic life of Offa people. The finding showed that the impact so far made, is significant. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0in; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->